Ethical challenges when intensive care unit patients refuse nursing care: A narrative approach - Bull, Eva Martine (Nursing ethics, 2016)
Background:Less sedated and more awake patients in the intensive care unit may cause ethical challenges.Research objectives:The purpose of this study is to describe ethical challenges registered nurses experience when patients refuse care and treatment.Research design:Narrative individual open interviews were conducted, and data were analysed using a phenomenological hermeneutic method developed for researching life experiences.Participants and research context:Three intensive care registered nurses from an intensive care unit at a university hospital in Norway were included.Ethical considerations:Norwegian Social Science Data Services approved the study. Permission was obtained from the intensive care unit leader. The participants’ informed and voluntary consent was obtained in writing.Findings:Registered nurses experienced ethical challenges in the balance between situations of deciding on behalf of the patient, persuading the patient and letting the patient decide. Ethical challenges were related to patients being harmful to themselves, not keeping up personal hygiene and care or hindering critical treatment.Discussion:It is made apparent how professional ethics may be threatened by more pragmatic arguments. In recent years, registered nurses are faced with increasing ethical challenges to do no harm and maintain dignity.Conclusion:Ethically challenging situations are emerging, due to new targets including conscious and aware critical care patients, leaving an altered responsibility on the registered nurses. Reflection is required to adjust the course when personal and professional ideals no longer are in harmony with the reality in the clinical practice. RNs must maintain a strong integrity as authentic human beings to provide holistic nursing care.